Antifungal effect of Hyptis suaveolens oil microemulsion based carboxymethyl mungbean gel for topical delivery - Ruttiros Khonkarn (2018)
© 2015, International Journal of Pharmacy and Pharmaceutical Science. All rights reserved. Objective: Conventional topical antifungal formulations limit the effectiveness of antifungal therapy. The aim of this study was to formulate effective antifungal microemulsion of H. suaveolens oil based carboxymethyl mungbean (CMMS) gel. Methods: H. suaveolens oil was obtained by steam distillation. Standard of H. suaveolens oil was performed by gas chromatography mass spectrometry (GC/MS). A high-viscosity CMMS was prepared and its mucoadhesive property was determined using modified USP dissolution test apparatus. H. suaveolens oil microemulsion based CMMS gel as transdermal drug carrier was then developed. Finally, in vitro drug release study and antifungal activity were determined. Results: GC/MS analysis exhibited that β-Caryophyllene, Sabinene and Limonene are the major components of H. suaveolens oil. CMMS gel revealed good mucoadhesive potential which depended on pH of the medium. A higher retention time in pH 4.5 medium than pH 10 medium was observed. Clotrimazole-loaded H. suaveolens oil microemulsions based CMMS gel was successful prepared and in vitro sustained release of clotrimazole was determined. Clotrimazole-loaded H. suaveolens oil microemulsions based CMMS gel had potent antifungal activity against all studied dermatophytes and Candida albican with higher inhibition zone than H. suaveolens oil microemulsions based CMMS gel, H. suaveolens oil and commercial clotrimazole cream. Conclusion: H. suaveolens oil microemulsions based CMMS gel present promising as an effective alternative for topical delivery of antifungal agents.